Transforming Akidah Akhlak Teaching Materials into VCT-Based E-Modules for Character Internalization in the Digital Era: A Systematic Literature Review - Ahmad Dimyati Ridwan; Syahidin; Mokh. Iman Firmansyah (Academic Bright Collaboration, 2026)
Purpose – Digital disruption has escalated moral degradation, notably indiscipline and a diminished work ethic among Generation Z, while conventional Akidah Akhlak learning heavily relies on textual indoctrination. Therefore, this study examines the urgency of transforming printed materials into Value Clarification Technique (VCT)-integrated E-Modules to internalize the character values of discipline and hard work (ikhtiar).Methods – Using a Systematic Literature Review (SLR), 20 core articles were rigorously analyzed from an initial pool of 87 studies retrieved from Scopus, Sinta, and Garuda (2021–2026).Findings – Results highlight that VCT systematically transitions students from moral knowing to moral action. The proposed E-Module conceptualizes this transition through concrete pedagogical features: Digital Storytelling, Interactive Dilemma Boards, Private Journaling, and Action Trackers, corresponding to the VCT stages. Research implications – Ultimately, developing this VCT-based E-Module provides an evidence-informed design direction for madrasahs to cultivate resilient, high-integrity graduates.Originality – Although yet to be empirically tested, this architectural integration provides an evidence-informed conceptual framework to proactively counteract digital escapism.